Management of Bacterial leaf blight of rice caused by Xanthomonas oryzae pv. oryzae through Integrated approach in western undulating zones of Odisha - Srujani Behera; Sunita Behera; Nayak, B S (Journal of Cereal Research, 2024)
Bacterial leaf blight (BLB) is considered as a major threat to rice production because of its wide spread, distribution and its destructiveness under favourable conditions. The disease is caused by Xanthomonas oryzae pv. oryzae is one of the most serious diseases in irrigated and rain fed environment in Asia and cause considerable loss. Thus, pooled data of experiments conducted at Regional Research and Transfer Technology Station, Bhawanipatna, OUAT for two years during 2021-22 and 2022-23 to know the efficacy of different commercially available fungicides, antibacterial chemicals and bio-agents against the bacterial leaf blight of rice. Results indicated that, seedling root dip treatment with Pseudomonas fluorescens @10gm/lt, 1st spray with P. fluorescens, 2ndspray with  Streptocyclin+CuOCl2 and 3rd spray with P. fluorescens at 15 days interval found to be best with lowest PDI (9.44%) and highest yield (42.0q/ha) with B:C ratio 1.89 followed by seedling root dip treatment with Streptocyclin@1gm/10lt and three times foliar spraying along with CuOCl2 @ 3gm/lt at 15days interval with PDI (16.78%) and yield 40.53 q/ha with B:C ratio 1.83 when compared to untreated control which has recorded the maximum PDI of 78.39 % and minimum yield 23.07 q/ha with lowest B:C ratio 1.12.